Legal Renewing of Consumer Protection (Himâyah Al-Mustahlaki) Through Islamic Law Perspective - Susanto, Burhanudin; Mohd Ruslan, Ros Amira binti (al-'adalah, 2019)
The purpose of this paper is to offer the concept of reforming consumer protection law (himâyah al-mustahlaki) through the perspective of Islamic law. To achieve this goal the author uses the integration of science as a method of analyzing from normative legal research by combining the statute and conceptual approaches. Although in the shari’a does not mention the term consumer directly, it contains principles that if carried out by business actors can provide protection to consumers. The potential loss inherent in consumers is generally divided into two, namely (1) Material losses (al-khasârah al-mâdiyah) both in the form of financial and non-financial assets; and (2) Humanity loss (al-khasârah al-insâniyah) both in the form of body and spirit. The overall potential loss needs to be accommodated in an integrated legislation to better guarantee legal certainty for consumers. The implementation of consumer protection can be realized through preventive treatment through fostering awarenes